Hubungan Kinerja Pertugas Posbindu PTM dengan Kepatuhan Kontrol Penderita Hipertensi - Ruslang Ruslang; Anugerah Yanuar Azis; Khaeriah B; Islamia Islamia; Nurhikmah Wijaya (Journal Research of Health Administration and Public Health (JRHAPH), 2025)
Hypertension is a non-communicable disease that poses a public health problem due to its contribution to high morbidity and mortality rates. In Indonesia, the prevalence of hypertension continues to rise, necessitating early detection efforts and effective management through programs such as Posbindu PTM. The performance of Posbindu PTM officers is considered an important factor that can influence the adherence of hypertension patients to routine check-ups. This study aims to determine the relationship between the performance of Posbindu PTM officers and the adherence to hypertension control among patients in Woronge Village. This research uses a cross-sectional approach with a purposive sample of 10 respondents. Data was collected through questionnaires and analyzed using Fisher's Exact Test. The results showed that 60% of the officers performed well, and 60% of the hypertension patients adhered to control. Bivariate analysis found a significant relationship between officer performance and control adherence, with a p-value of 0.048 (p < 0.05). Therefore, the performance of Posbindu PTM officers has a significant impact on the adherence of hypertension patients to health control. This highlights the importance of officers' roles in providing education and motivation to hypertension patients to ensure they follow health control routines. To achieve this, there is a need to improve the quality of officers' performance through training and strengthening monitoring systems at Posbindu PTM. Additionally, it is also important to engage the community more actively in this program, so they become more aware of the importance of sustainable hypertension management. Intensive training for officers and improvement of Posbindu PTM facilities can further support the success of this program.